'It's meant to make you laugh': Wittgenstein's joke book and Joyce's Finnegans Wake. Issue 4 (3rd April 2021) - Greene, Darragh
ABSTRACT: Ludwig Wittgenstein once remarked that a serious and good philosophical book could consist entirely of jokes. James Joyce's Finnegans Wake is that book. Wittgenstein's late philosophy, exemplified by Philosophical Investigations, aims to show the complexity of language through the descriptive category of the language-game. Language has no secret nature or essence; instead, there are countless kinds of language-games that construct both common and strange forms of life. The Wake through its series of puns, neologisms, compounds, and riddles shows exactly the play of Wittgensteinian language-games. By exposing the fundamental operations of language in a displayed matrix of new language-games, the Wake fascinates us, and, at the same time, shows us the source of our fascination with language. The Wakean rules of the game are as complex and manifold as the labyrinth of life. The universal key to solving the maze is laughter. When the Wake 's 'thistlewords in their garden nursery' are read in the right spirit, by getting the jokes, and laughing at them, the reader learns how language makes the world and is freed from its snares and bewitchment.